2009
DOI: 10.1002/prot.22470
|View full text |Cite
|
Sign up to set email alerts
|

Molecular determinants of the pKa values of Asp and Glu residues in staphylococcal nuclease

Abstract: Prior computational studies of the acid-unfolding behavior of staphylococcal nuclease (SNase) suggest that the pK(a) values of its carboxylic groups are difficult to reproduce with electrostatics calculations with continuum methods. To examine the molecular determinants of the pK(a) values of carboxylic groups in SNase, the pK(a) values of all 20 Asp and Glu residues were measured with multidimensional and multinuclear NMR spectroscopy in an acid insensitive variant of SNase. The crystal structure of the prote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

21
314
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 161 publications
(335 citation statements)
references
References 85 publications
21
314
0
Order By: Relevance
“…3C). One crystallographic water molecule occupies a small recess extending inwards between β-1 and α-1; an analogous water molecule was observed previously in the structure of the Δ+PHS protein (16). Other than this semiburied water molecule, there are no polar atoms within 4.5 Å of either carboxyl oxygen of the Glu side chain, leaving several potential hydrogen bonds unsatisfied.…”
Section: Resultssupporting
confidence: 54%
See 1 more Smart Citation
“…3C). One crystallographic water molecule occupies a small recess extending inwards between β-1 and α-1; an analogous water molecule was observed previously in the structure of the Δ+PHS protein (16). Other than this semiburied water molecule, there are no polar atoms within 4.5 Å of either carboxyl oxygen of the Glu side chain, leaving several potential hydrogen bonds unsatisfied.…”
Section: Resultssupporting
confidence: 54%
“…In these models the favorable Coulomb interaction between the charges in the buried pair is never strong enough to offset the unfavorable self-energy experienced by the two buried charges. In some microscopic models, Coulomb interactions can be stronger than dehydration effects, but calculations with these methods are still suspect as they cannot reproduce self-energies reliably (14, 15) and tend to overestimate the magnitude of Coulomb interactions (14,(16)(17)(18). The experiments that were performed test assumptions made in most continuum methods, including the idea that a pair of ionizable groups interacting at close range in a dehydrated environment can be treated classically as point charges without invoking some level of quantum mechanical treatment to account for polarizability and for the properties of a proton shared between acidic and basic moieties interacting over a short distance in a highly dehydrated environment (19,20).…”
mentioning
confidence: 99%
“…pK a measurements report native state electrostatic energetics and are a sensitive probe of the effect of mutations (35). The pK a values are identical in the two proteins, indicating that the mutation does not perturb native state electrostatic interactions involving the acidic side chains (Table S4) (21,24 The thermodynamic studies indicate that K12 is coupled to a multitude of hydrophobic sites.…”
Section: Resultsmentioning
confidence: 99%
“…A theoretical calculation has shown that Glu451 presents an unusually high pK a of 9.9 (Bello et al, 2012), which is probably the result of interactions with other carboxylic groups at the TNC (Harris & Turner, 2002;Castañ eda et al, 2009). Accordingly, the perturbed pK a value of Glu451 seems to be governed by its interaction with the Asp452 residue (pK a = 4.40, as calculated using the PROPKA server; Olsson et al, 2011), which is at a hydrogen-bonding distance of 3.14 Å from Glu451a O "2 (Fig.…”
Section: Methionine-rich B-hairpin Motifmentioning
confidence: 99%